Amber's Other Grandparents - Bonnici, Peter (The Bodley Press Ltd, 1985)
When Amber's Indian grandparents come to stay, she notices that Grandpa's English is very strange and that only Mother can understand Grandma but it isn't long before she decides she likes her other grandparents after all.
Keywords: Family; Juvenile Fiction; Multigenerational